Worth the wait? How restaurant waiting time influences customer behavior and revenue. Issue 1 (21st May 2018) - De Vries, Jelle; Roy, Debjit; De Koster, René
Abstract: In many service industries, customers have to wait for service. When customers have a choice, this waiting may influence their service experience, sojourn time, and ultimately spending, reneging, and return behavior. Not much is known however, about the system‐wide impact of waiting on customer behavior and resulting revenue. In this paper, we empirically investigate this by analyzing data obtained from 94, 404 customers visiting a popular Indian restaurant during a 12 month period. The results show that a longer waiting time relates to reneging behavior, a longer time until a customer returns, and a shorter dining duration. To find out the impact of the consequences of waiting time, we use the empirical findings and data collected in a simulation experiment. This experiment shows that, without waiting, the total revenue generated by the restaurant would increase by nearly 15% compared to the current situation. Stimulating customers to reserve could enable restaurants to reap part of this benefit. Furthermore, the results of simulation experiments suggest that, within the boundaries of the current capacity, revenue could be increased by a maximum of 7.5% if more flexible rules were used to allocate customers to tables. Alternatively, by increasing the existing seating capacity by 20%, revenue could be boosted by 7.7% without the need to attract additional customers. Our findings extend the knowledge on the consequences of customer waiting, and enable service providers to better understand the financial and operational impact of waiting‐related decisions in service settings.